EFFECT OF INTEGRATED WEED MANAGEMENT ON FIBER QUALITY CHARACTERS OF SOME COTTON CULTIVARS - & Hammood, Al-Chalabi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was conducted at the experimental field, Department of Field Crop Science - College of Agriculture Abu-Ghraib- University of Baghdad, during summer season at 2012 and 2013, to determine the extent of the impact of Integrated Weed Management (IWM) By reducing herbicide use and re-distribution of plants as reflected on fiber quality characters of some cotton cultivars . A randomized complete block design (RCBD) arranged according to split-plot was used with three replicates , included six weed control treatments as Main-plots where as Sub-plots included eight cotton cultivars. The results showed that treatments of weedfree achieved highest lint length, lint strength , lint fineness . The treatment of weedfree with normal crop density of 106667 plant.h-1 achieved highest lint length of 27.62 , 28.15 mm , lint strength of 19.00 , 19.09 g.Tex-1 , and lint fineness of 3.04 , 3.19 micronaire, at both seasons respectively, where as the treatment of weedfree with high crop density of 200000 plant.h-1 achieved lint length of 26.96 , 27.47 mm , lint strength of 18.12 , 18.32 g.Tex-1 , and lint fineness of 2.50 , 2.94 micronaire, at both seasons respectively, treatment of trifluralin with recommended rate of 2.4 L.h-1 applied with normal crop density of 106667 plant.h-1 achieved lint length of 26.70 , 27.24 mm , lint strength of 18.04 , 18.25 g.Tex-1 , and lint fineness of 2.79 , 2.94 micronaire at both seasons and these values were approaches to that values achieved by the treatment of half rate of trifluraline 1.2 L.h-1 applied with high crop density of 200000 plant.h-1 which achieved lint length of 26.36 , 26.78 mm, lint strength of 17.50 , 17.65 g.Tex-1 , and lint fineness of 2.67 , 2.81 micronaire respectively at both seasons. Different cotton cultivars showed various fiber quality characters , however Ashur-1 cultivar in weedy treatment with high crop density of 200000 plant.h-1 gave highest rates of lint length, lint strength, and lint fineness, reflect competition ability of this cultivar to a companion weeds in this treatment . Similarity and achieved high means of fiber characters in the treatment of half recommended rate of trifluralin 1.2 L.h -1 with high crop density of 200000 plant.h-1 confirmed the integrated effect of the cultivars , herbicide , and crop density for improve fiber characters and these variables may consider as important factors for integrated weed management in cotton crop .